2015
DOI: 10.1016/j.jvs.2015.06.133
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of surgeon-modified fenestrated-branched endograft repair for acute aortic pathology

Abstract: Objective Open surgical repair for acute aortic pathologies involving the visceral vessels is associated with morbidity and mortality rates of 40% to 70% and 30% to 60%, respectively. Due to these poor outcomes, the application of fenestrated/branched endovascular aortic repair (F/B-EVAR) has been expanded in this setting; however, durability remains unknown. The purpose of this analysis was to describe outcomes after F/B-EVAR for acute aortic disease. Methods A single center retrospective review of all F/B-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…However, it is evident that EVAR-c confers higher risk in the nonelective situation and may justify our bias to attempt endovascular salvage techniques in selected patients to reduce mortality similarly to how EVAR has begun to supplant open repair of native ruptured AAA. 32,33 Further, preoperative identification of the clinical and procedure-specific predictors may provide important risk stratification for clinicians that can inform operative decision making and patient and family counseling. Decisions regarding aortic cross-clamp placement and the effect on renal/visceral ischemia time can be factored into the operative plan when possible to reduce postoperative morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is evident that EVAR-c confers higher risk in the nonelective situation and may justify our bias to attempt endovascular salvage techniques in selected patients to reduce mortality similarly to how EVAR has begun to supplant open repair of native ruptured AAA. 32,33 Further, preoperative identification of the clinical and procedure-specific predictors may provide important risk stratification for clinicians that can inform operative decision making and patient and family counseling. Decisions regarding aortic cross-clamp placement and the effect on renal/visceral ischemia time can be factored into the operative plan when possible to reduce postoperative morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Uncovered stent branches exhibit higher rates of problems than covered stent branches, mostly from in-stent stenosis 5 ; however, no particular stent graft has been shown to be more effective or durable as a branch device than others. The failure modes of branches include stent kinking, stent fracture, device migration, material fatigue, thrombosis, and neointimal hyperplasia 6, 7. A retrospective study of fenestrated aortic endografts reported that 34% of grafts experienced either proximal or distal migration, but there was no significant association between graft migration and kinking or component fractures 8 .…”
Section: Discussionmentioning
confidence: 99%
“…3,8 In a previous systematic review of 23 reports containing 308 patients treated between 1999 and 2015 for complex aortic aneurysm, outcomes overall were similar for off-the-shelf fenestrated/branched stent-grafts and PMEGs, including technical success of 95% and 91%, mortality of 1.1% vs 3.5%, and target vessel patency of 98% vs 97%, respectively. 9 Since that review, many additional studies (those with ≥10 cases) citing the use of PMEGs have been published, [1][2][3][4][5]7,8,[10][11][12][13][14][15] though some updated earlier populations within investigation device exemption (IDE) protocols 2,3,13 or earlier single-center reports. 4,5,7,10 Excluding 4 duplicate studies (103 cases) 8,[13][14][15] and another 101 patients presented earlier, 9 375 new cases not incorporated in the previous review were identified since March 31, 2015 (a 100% increase), even though in some qualified centers the use of PMEGs declined from 66% between 2011 and 2013 to 4% between 2014 and 2016.…”
Section: Pmegsmentioning
confidence: 99%
“…Overall, 9 additional single-center studies were found (Table 1), [1][2][3][4][5]7,[10][11][12] 3 of them conducted within an IDE trial, 2,3,12 with a total of 476 patients (339 men, 71.2%). Few of these compared outcomes between PMEGs and company-manufactured devices 3,5,7 and hybrid techniques.…”
Section: Pmegsmentioning
confidence: 99%